The Effect of Sanitation on Stunting Prevalence in Indonesia - Nizaruddin Nizaruddin; M. Irsyad Ilham (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2022)
Preparing children from birth can boost productivity and competitiveness later in their lives. However, the occurrence of malnutrition and stunting during childhood period will reduce their productivity and increases the risk of non-communicable diseases later in their lives. This study examines the effect of sanitation, drinking water sources, and drinking water treatment on stunting in Indonesian children (0-59 months). This study analyses cross- sectional data from the 2014 Indonesia Family Life Survey (IFLS) 5 with 3,834 children living with their biological mothers. The Logistic Regression to estimate the coefficients is applied here. The results show that the variables of sanitation, drinking water sources, and drinking water treatment before consuming affected stunting. Children who consume tap water are less likely to be stunted (OR=0.81, 95% CI 0.66-0.99). Birth weight, economic conditions, and mother’s level of education also affect risk of stunting. Hence, to overcome the risk of stunting, the government have to accelerate the supply of basic sanitation, to protect the good quality of drinking water sources, and to promote the awareness of boiling water before consumption.